FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PENGELOLA KEUANGAN MELAKUKAN TINDAKAN WHISTLE –BLOWING (Studi Kasus Pada Universitas Bengkulu) - Dewi Sutrisni; Isma Coryanata (Jurnal Akuntansi, 2018)
This study aims to examine the influence of attitude factors on whistle-blowing, organizational commitment, personal cost, the degree of seriousness of fraud and the pressure of obedience to the interest of financial managers performing whistle-blowing action on the financial manager of Bengkulu University. The data used in this study is the primary data collected through survey method by distributing 106 questionnaires to the financial manager in Bengkulu University units. Questionnaires were made using two different cases resulting in different data processing results in each case. The results showed that in the first case only the attitude toward whistle-blowing that positively affect the interest of financial managers doing whistle-blowing action and 4 other variables have no effect. In the second case, the attitude toward whistle-blowing and the pressure of obedience have a positive effect on the interest of the financial managers perform whistle-blowing action while the organizational commitment variable, personal cost, the seriousness of the fraud does not affect the financial manager's interest in doing the whistle-blowing action. Discussions of the implications of the research results and their limitations have also been made.Key words: whistle-blowing, organizational commitment, personal cost, level of fraud seriousness, pressure of obedience